Hubungan Tingkat Depresi dengan Asupan Energi dan Protein Pasien Depresi Rawat Inap di Rumah Sakit Jiwa Daerah Dr Amino Gondohutomo Semarang - Uswatun Chasanah; Sufiati Bintanah; Yuliana Noor SU (Universitas Muhammadiyah Semarang, 2013)
Depression is a mental disorder caused by severe disappointments such as death, divorce, concerns, bankruptcy, death of a loved one is very marked symptoms of sadness, despair , loss of joy , fatigue and tiredness, lack of appetite , weight loss. In a state of depression decreased appetite, which could interfere with the absorption of nutrients into the body, especially the intake of energy and protein. Total case of depression is estimated over 150 million people. Based on a report in 2012 at the Regional Mental Hospital Dr. Amino Gondohutomo contained 5.86 % of 3821 inpatients suffering from depression . The purpose of the study was to determine the relationship of depression with levels of energy and proteinintake depressed patients hospitalized in the Regional Mental Hospital Dr. AminoGondohutomo Semarang This type of research is explanatory research, the research that explains the relationship between two or more variables studied . The method used was a cross-sectional , where the variables studied in the same time. Population of the study is that depressed patients hospitalized on 20 April to 20 June 2013 in the Regional Mental Hospital Dr. Amino Gondohutomo criteria Semarang aged 16 years and older. Samples were taken in non probabilitysampling technique with Consecutive Sampling. The results showed as many as 50% of depressed patients have both energy intake and 56.7 % of depressed patients have good protein intake. Data analysis using chisqure test result thatthe p - value (0.713 and 0.785)> 0:05 so that Ho is accepted it means there is no relationship between the level of depression with the energy and protein intake. This research should be developed further by adding other variables such as nutritional status or the duration of treatment. Keywords: Depression levels, energy intake, protein intake.